2007
DOI: 10.1523/jneurosci.0056-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Human Soluble Epoxide Hydrolase GeneEPHX2Linked to Neuronal Survival after Ischemic Injury

Abstract: Single nucleotide polymorphisms (SNPs) in the human EPHX2 gene have recently been implicated in susceptibility to cardiovascular disease, including stroke. EPHX2 encodes for soluble epoxide hydrolase (sEH), an important enzyme in the metabolic breakdown of arachidonic acid-derived eicosanoids referred to as epoxyeicosatrienoic acids (EETs). We previously demonstrated that EETs are protective against ischemic cell death in culture. Therefore, we tested the hypothesis that polymorphisms in the human EPHX2 gene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
82
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 33 publications
10
82
0
2
Order By: Relevance
“…15,36 In line with this, we have previously shown that brain EETs protect neurons against ischemia by mechanism(s) separate from cerebrovascular dilation in the absence of hyperglycemia. 40 Our current study supports a neuroprotective role of brain EETs that is likely independent of cerebral perfusion, this time in the context of hyperglycemia, as STZ decreased brain EET concentrations, while increasing infarct size without altering cerebral perfusion; effects that were reversed by sEH inhibition.…”
Section: Discussionsupporting
confidence: 81%
“…15,36 In line with this, we have previously shown that brain EETs protect neurons against ischemia by mechanism(s) separate from cerebrovascular dilation in the absence of hyperglycemia. 40 Our current study supports a neuroprotective role of brain EETs that is likely independent of cerebral perfusion, this time in the context of hyperglycemia, as STZ decreased brain EET concentrations, while increasing infarct size without altering cerebral perfusion; effects that were reversed by sEH inhibition.…”
Section: Discussionsupporting
confidence: 81%
“…4 PCRmediated deletion was used to remove the PTS of TAT-sEH-WT to create translocation deficient TAT-sEH-ΔPTS ( Figure 1A). Deletion of the PTS was verified by sequencing.…”
Section: Expression and Purification Of Tat-fusion Proteinmentioning
confidence: 99%
“…Recombinant proteins were expressed and purified as previously described. 4 Concentrations of purified fusion proteins were measured with a Bradford assay (Bio-Rad, Hercules, CA, USA). Protein purity and specificity was confirmed by immunoblotting.…”
Section: Expression and Purification Of Tat-fusion Proteinmentioning
confidence: 99%
See 2 more Smart Citations